Identifying candidate host plants for trap cropping against Drosophila suzukii in vineyards - Anne-Laure Fragnière; Sven Bacher; Patrik Kehrli (Journal of Pest Science, 2024)
The spotted wing drosophila (SWD), Drosophila suzukii Matsumura (Diptera: Drosophilidae), is a serious pest in vineyards where it is difficult to control. Trap cropping, which involves manipulating the host plant composition in the crop vicinity to lure the pest away from grapes and towards more attractive host plant fruits, might be an interesting but so far neglected control approach to limit SWD egg-laying in grapes. An ideal trap crop should be more attractive to the pest than the actual crop and should ideally restrict pest development. We determined the attractiveness of fruits of 60 plant species for SWD egg-laying and their suitability for larval development in laboratory assays. Compared to grapes, 16 of the 60 fruits were strongly preferred by SWD females for egg-laying and additionally inhibited the development of SWD larvae into adults. Host preference was strongly influenced by the hardness of the fruit skin, and larval development was marginally affected by the acidity of fruits. However, none of the measured fruit traits had a significant effect on the emergence success of SWD. All 16 candidate trap crop plants should be further tested for their potential to reduce SWD infestation of grapes. We provide practical advice on the next steps to be taken for implementing a successful trap cropping strategy against SWD in commercial vineyards.